2021
DOI: 10.1136/bcr-2020-240834
|View full text |Cite
|
Sign up to set email alerts
|

Complete heart block in cardiac sarcoidosis reversed by corticosteroid therapy: time course of resolution

Abstract: A 53-year-old man was admitted for recurrent syncope and found to have complete heart block (CHB). Cardiac magnetic resonance imaging MRI) showed extensive patchy late gadolinium enhancement in the apical and lateral walls, consistent with cardiac sarcoidosis (CS) but no scar in the septum. A fluorodeoxyglucose (FDG)–positron emission tomography showed FDG uptake in the septum and basal lateral walls. Imaging suggested active inflammation in the septum affecting atrioventricular (AV) conduction but no irrevers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Interestingly, two cases were found in which AV block appeared to be reversed by corticosteroid therapy alone. In one case, a patient with complete heart block reversed to second degree AV block Mobitz type II and later to normal AV conduction after four weeks of corticosteroids treatment, and in the second case, a patient with complete heart block reversed to first degree AV block after two months of corticosteroid treatment [ 18 - 19 ]. While unable to be explored in our above case, it may be worth exploring the viability of medical monotherapy as a standalone treatment for CS, which offers the ultimate benefit of alleviating emotional, financial, and logistical burdens of cardiac device placement and its lifetime potential for further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two cases were found in which AV block appeared to be reversed by corticosteroid therapy alone. In one case, a patient with complete heart block reversed to second degree AV block Mobitz type II and later to normal AV conduction after four weeks of corticosteroids treatment, and in the second case, a patient with complete heart block reversed to first degree AV block after two months of corticosteroid treatment [ 18 - 19 ]. While unable to be explored in our above case, it may be worth exploring the viability of medical monotherapy as a standalone treatment for CS, which offers the ultimate benefit of alleviating emotional, financial, and logistical burdens of cardiac device placement and its lifetime potential for further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that SN abnormalities were irreversible even in those who received immunosuppressants and that ICD implantation with significant atrial pacing was necessary for patients with probable late-stage CS. 3–5 Therefore, early diagnosis and prompt initiation of treatment are important to prevent the progression of early- to late-stage CS to aid with the recovery of SN and AV conduction 11 and to avoid pacemaker implantation, considering that CS may occasionally be rapidly progressive. 1 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Complete AV block has a prevalence of 23% to 30% in patients with cardiac sarcoid 51 . The administration of corticosteroids may reverse the AV block caused by sarcoid if active inflammation (as opposed to fibrosis) is present 65 …”
Section: Extrinsic Causesmentioning
confidence: 99%
“…51 The administration of corticosteroids may reverse the AV block caused by sarcoid if active inflammation (as opposed to fibrosis) is present. 65 Endocrine Diseases Among endocrine diseases, hyperthyroidism is rarely responsible for CHB. Focal myocarditis, interstitial inflammation, fibrosis, myocyte necrosis, in, and around the AV node have been reported.…”
Section: Infiltrative Diseasesmentioning
confidence: 99%